Weak+Vacuum and One Decoy States with Two Way Quantum Key Distribution Protocol - Abdul Khir, M. F.; Bahari, I.; Ali, Sellami; Shaari, S. (World Scientific, 2013)
We present relevant bounds for the case of weak+vacuum decoy state and one decoy state for a two-way four states Quantum Key Distribution (QKD) protocol. The numerical simulation result is significant given that an improvement in maximum secure distance of nearly twice the original one is achieved.